Maternal and fetal outcome among patients with short inter-pregnancy interval - Khatoon, Saima; Mehmoodah, Mehmoodah; Hanif, Maria; Asgar, Shakeela; Manzor, Sahrish (Journal of Neonatal Surgery, 2025)
Objective: To determine the frequency of low birth weight, preterm birth and anemia in anemia in pregnant women’s with short inter-pregnancy interval. Material & Methods Study Design: It was cross sectional study Setting: Gynaecology and Obstetrics department, Shaikh Zayed Women Hospital, Larkana. Duration: 6 months after the approval of synopsis i.e. from 13th March, 2018 to 13th September, 2018. Data collection: 301 females were enrolled. Maternal outcome (Anemia) and fetal outcome (pre-term birth and low birth weight) in short interval pregnant females was noted. All the collected data was entered and analyzed on SPSS version 20. Results: The mean age of females was 31.93±6.52 years and the mean Hb was 8.54±1.79. Anemia was found in 255(84.7%) females, the preterm birth babies were 130(43.2%) and the low birth weight babies were 151(50.17%). Conclusion: This study showed the anemia 84.7% females, the preterm birth babies were 43.2% and low birth weight babies were 50.17% in females presenting with short inter-pregnancy interval.